A provably secure ECC-based access and handover authentication protocol for space information networks. (1st November 2021) - Guo, Junyan; Du, Ye; Zhang, Yahang; Li, Meihong
Abstract: At present, space information networks are widely used in various fields and gradually attract more and more users to access. However, because the wireless channel in space information networks is public, it is extremely vulnerable to attacks such as eavesdropping, replay and impersonation attacks, which may lead to the leakage of privacy and secret information. In recent years, many authentication schemes have been proposed to prevent malicious nodes from accessing and stealing resources, but most of these schemes either do not take into account the security of satellite relay nodes or the handover problems caused by dynamic topology. To solve the above-mentioned problems, we propose a novel ECC-based authentication scheme, which not only confirms the validity of the satellite node when user and ground station authenticate each other, but also designs the handover schemes based on two possible signal handover scenarios. For the handover involving the ground station, we also design an efficient multi-user batch handover authentication scheme, which can greatly reduce the computation overhead and delay. In the security analysis, we prove the security of our protocol based on the ROM model and AVISPA formal verification tool, and verify that our protocol can meet the security attributes and resist various forms of attacks through informal security analysis. Finally, security and performance analysis results demonstrate that our protocol is more suitable for user access and handover in space information networks while ensuring higher security requirements.